2016
DOI: 10.1007/s00018-016-2168-3
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule plus-end tracking proteins in neuronal development

Abstract: Regulation of the microtubule cytoskeleton is of pivotal importance for neuronal development and function. One such regulatory mechanism centers on microtubule plus-end tracking proteins (+TIPs): structurally and functionally diverse regulatory factors, which can form complex macromolecular assemblies at the growing microtubule plus-ends. +TIPs modulate important properties of microtubules including their dynamics and their ability to control cell polarity, membrane transport and signaling. Several neurodevelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 286 publications
(263 reference statements)
3
57
0
Order By: Relevance
“…The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear. Mutations in genes encoding tubulin isoforms and different microtubule regulators including +TIPs have also been associated with neurodevelopmental diseases, including disorders of neuronal migration (Breuss and Keays, 2014;Chakraborti et al, 2016;van de Willige et al, 2016), and it will be interesting to investigate which of their functions reflect general mechanisms of 3D cell motility and which are neuron specific.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…The expression or function of other microtubule regulators, such as survivin Rosa et al, 2006), ATIP3 (Molina et al, 2013;Velot et al, 2015) and the +TIPs EB1 (Liu et al, 2009;Stypula-Cyrus et al, 2014) and APC (Etienne-Manneville, 2009), was found to be altered in certain cancers, but the exact role of these proteins in 3D cell migration is still unclear. Mutations in genes encoding tubulin isoforms and different microtubule regulators including +TIPs have also been associated with neurodevelopmental diseases, including disorders of neuronal migration (Breuss and Keays, 2014;Chakraborti et al, 2016;van de Willige et al, 2016), and it will be interesting to investigate which of their functions reflect general mechanisms of 3D cell motility and which are neuron specific.…”
Section: Microtubule Alteration and Diseases Related To Cell Migrationmentioning
confidence: 99%
“…They can autonomously track growing microtubule plus ends recognizing a structural cap (van de Willige et al, 2016) and are useful markers for polymerizing microtubule tips in axons (Stepanova et al, 2003). EBs target numerous other +TIPs to the tips of polymerizing microtubules (Kumar and Wittmann, 2012).…”
Section: Microtubule Plus End Associated Proteinsmentioning
confidence: 99%
“…2) (Akhmanova and Steinmetz, 2010, Akhmanova and Steinmetz, 2015, van de Willige et al, 2016). Strikingly, no reports so far seem to have pinpointed a single master +TIP of polymerisation, the absence of which would cause the total or next to complete loss of MTs.…”
Section: The Mt De/polymerisation Machinery At Mt Plus Endsmentioning
confidence: 99%
“…The contributions of individual hitchhikers to MT plus end dynamics remain little understood (Akhmanova and Steinmetz, 2010, Akhmanova and Steinmetz, 2015, van de Willige et al, 2016). Reported mutant phenotypes tend to be subtle and often inconsistent, and their impact on MT dynamics may be indirectly influenced by additional cellular functions of these proteins (for example, APC acts as an actin nucleator) (Okada et al, 2010).…”
Section: The Mt De/polymerisation Machinery At Mt Plus Endsmentioning
confidence: 99%